2014
DOI: 10.1584/jpestics.d14-033
|View full text |Cite
|
Sign up to set email alerts
|

Action mechanism of the novel rice blast fungicide tolprocarb distinct from that of conventional melanin biosynthesis inhibitors

Abstract: The target site of tolprocarb, a novel systemic fungicide used for controlling rice blast, was investigated. Tolprocarb decolorized the mycelia of Magnaporthe grisea; the decolorization was reversed by adding scytalone or 1, 3,6,3,6,. This result suggested that the target site of tolprocarb was polyketide synthase (PKS), which regulated polyketide synthesis and pentaketide cyclization in melanin biosynthesis. Further, we produced a transgenic Aspergillus oryzae, which possessed the PKS gene of M. grisea, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 22 publications
1
26
0
1
Order By: Relevance
“…16) Tolprocarb developed by Mitsui Chemicals Agro, Inc., showed a high controlling effect on rice blast by both nursery-box application and broadcasting on paddy rice. 19) In our previous paper, 20) we demonstrated that tolprocarb inhibited PKS activity with an IC 50 =0.03 µM. In the present study, a series of tolprocarb derivatives were evaluated for PKS-A, MBI-A, and RBC-E. A linear relationship with r 2 =0.90 between PKS-A and MBI-A was evident.…”
Section: Discussionmentioning
confidence: 51%
See 3 more Smart Citations
“…16) Tolprocarb developed by Mitsui Chemicals Agro, Inc., showed a high controlling effect on rice blast by both nursery-box application and broadcasting on paddy rice. 19) In our previous paper, 20) we demonstrated that tolprocarb inhibited PKS activity with an IC 50 =0.03 µM. In the present study, a series of tolprocarb derivatives were evaluated for PKS-A, MBI-A, and RBC-E. A linear relationship with r 2 =0.90 between PKS-A and MBI-A was evident.…”
Section: Discussionmentioning
confidence: 51%
“…MICs for MBI-A were determined by visually observing the mycelial color change because melanin synthesized in the mycelia can be observed as dark gray, and the inhibition of melanin biosynthesis, such as the addition of tolprocarb, yields colorless mycelia. 20) A distinct growth inhibition was not observed in the melanin biosynthesis inhibitory assay with all compounds studied here. …”
Section: Melanin Biosynthesis Inhibitory Assay Using a Potato Dextrosementioning
confidence: 71%
See 2 more Smart Citations
“…The blocking of the melanin biosynthesis in pathogenic fungi can result in the loss of their pathogenicity and an increased susceptibility of fungi to biotic and abiotic stresses [7,8,9]. For example, a defect in one of the PKS-encoding genes of A. flavus resulting in a formation of non-pigmented sclerotia significantly increased the susceptibility of the fungus to the deleterious effect of UV light and heat; in addition, the melanin-deficient mutant was less resistant to insect predation as compared with the wild-type strain generating melanized sclerotia [10].…”
Section: Introductionmentioning
confidence: 99%